PEMBINAAN TERHADAP NARAPIDANA RESIDIVIS TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA : (SUATU PENELITIAN DI RUTAN KELAS IIB TAPAKTUAN) - Arifa, Ridha Nur (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2024)
The definition of coaching according to Law Number 22 of 2022 concerning Corrections is an activity carried out to improve the quality of personality and independence of prisoners and assisted children which aims to improve the quality of personality and independence of inmates so that they realize mistakes, improve themselves and not repeat criminal acts, so that can be accepted again by the community, can live normally as a good, law-abiding, responsible citizen, and can play an active role in development; and provide protection to the community from repetition of criminal acts. However, in reality, in the Class IIB Tapaktuan Detention Center, there are still many repeat crimes of narcotics abuse. This paper examines the implementation of training for recidivist prisoners for the crime of narcotics abuse in the class IIb detention center in Tapaktuan and the effectiveness of training for prisoners recidivist for the crime of narcotics abuse in the class IIb detention center in Tapaktuan. Based on the discussion above, it can be concluded that the implementation of guidance for criminal recidivists is in accordance with applicable laws and regulations, but the implementation has not been effective due to the limited skills possessed by officers, the lack of facilities in the Tapaktuan Class IIB Detention Center and the lack of The awareness of the perpetrators is that there are still very few prisoners who are conscious and willing to learn.